New Progress on Fiber-Based Thermoelectric Materials: Performance, Device Structures and Applications - Yanan Shen (MDPI AG, 2021)
With the rapid development of wearable electronics, looking for flexible and wearable generators as their self-power systems has proved an extensive task. Fiber-based thermoelectric generators (FTEGs) are promising candidates for these self-powered systems that collect energy from the surrounding environment or human body to sustain wearable electronics. In this work, we overview performances and device structures of state-of-the-art fiber-based thermoelectric materials, including inorganic fibers (e.g., carbon fibers, oxide fibers, and semiconductor fibers), organic fibers, and hybrid fibers. Moreover, potential applications for related thermoelectric devices are discussed, and future developments in fiber-based thermoelectric materials are also briefly expected.